Foreign debt and capital accumulátion - Horst Siebert (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1987)
In an open economy, a country may borrow in order to accumulate capital. The paper compares the case of foreign borrowing with a scenario in which a country accumulates capital internally by postponing consumption. The impact of borrowing on the time profile of consumption and of debt is analyzed. The model also specifies the time profile of the balance of trade. The opportunity costs of borrowing are studied and conditions are specified in which it is worthwhile to borrow. In the context of the model, some phenomena are discussed that may make it more difficult for the debtor country to pay interest and repay debt and that may be an inducement to breach the credit contract.
Keywords: 330